Konsumsi Makanan Halal Perspektif Antropologi - Takhim Muhamad Takhim; Risti Lia Sari (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2022)
Food which is a dhoruri (basic) human need, is used for the continuity and existence of life. The need for adequate nutritional and vitamin content, food must also pay attention to other aspects. This becomes something crucial when related to anthropology, how human behavior, the environment, the way of family life, settlement patterns, economic and political systems, culture, religion, and so on become integrity that can shape a new human civilization. When linked to economics and politics, halal food can be a source of income and foreign exchange. When associated with culture, halal food becomes a unique and interesting aspect in various forms that are carried out in various ceremonies, rituals, and others. When it comes to religion, there are mandatory rules (obligations) to consume it. This is then integrated and becomes the behavior of the community. This research uses a qualitative method with a literature study digging from various sources of books, journals, newspapers, and others that are relevant, then processed and analyzed to make conclusions. The results of the study state that the struggle for aspects of social culture, and religion accompanied by the development of science and technology has changed human behavior to become a new entrepreneur in the field of halal culinary and has created a consumptive culture in society.